Evaluating reinforcement loading within surcharged segmental block reinforced soil walls using a limit state framework. Issue 6 (December 2016) - Xie, Yonggui; Leshchinsky, Ben; Yang, Shangchuan
Abstract: Internal design of Mechanically Stabilized Earth (MSE) Walls are frequently based on lateral earth pressure methods. A key component of limit state design includes determination of the necessary resisting forces of reinforcements to enable stability and function of the internal reinforcing components. However, conventional methods (e.g. Rankine) are not directly applicable when accounting for surcharge loading that is non-uniform, often manifested by the presence of strip footings placed directly on the reinforced soil. Within this study, an approach is presented to determine the reactive loads in individual reinforcements, Tmax, using limit analysis (LA) considering a log-spiral mechanism and the effects of facing elements for segmental block reinforced soil walls. Lateral earth pressures attained from this approach are consistent with simplified analyses presented in the literature, realizing reinforcement loads that are more reasonable when compared with observed reinforcement loading than conventional limit equilibrium-based methods. To demonstrate the effects of various design parameters, the relationship between soil strength properties, interface friction between the soil, facing and toe, wall height, wall batter and reinforcement loads were studied.